Development and Validation of Tadalafil Determination in Human Plasma by HPLC-MS Method - D. S. Bogdanova; T. N. Komarov; I. E. Shohin; E. S. Melnikov; O. A. Miskiv; Yu. V. Medvedev (Разработка и регистрация лекарственных средств, 2019)
Introduction. Tadalafil is a drug used to treat erectile dysfunction. For the quantitative determination of tadalafil in human plasma are used methods of high performance liquid chromatography with ultraviolet and tandem mass spectrometric detection, during the analytical part of pharmacokinetic studies. In the majority of the considered methods the method of liquid-liquid extraction and the method of solid-phase extraction are used, these methods are difficult and expensive. Therefore, the method of protein precipitation was considered as sample preparation. This method is simple and there is important to analysis a lot of clinical samples in bioequivalence studies.Aim. The aim of this study is to develop method for the quantitative determination of tadalafil in human plasma by HPLC-MS for the analytical part of pharmacokinetic studies.Materials and methods. Quantitative determination of tadalafil in plasma by HPLC-MS. A sample was prepared using acetonitrile protein precipitation.Results and discussion. This method was validated by next validation parameters: selectivity, matrix effect, calibration curve, accuracy, precision, lower limit of quantification, carry-over and stability.Conclusion. The method of the quantitative determination of tadalafil in human plasma was developed and validated by HPLC-MS. The analytical range of the was 5,00–1000,00 ng/ml tadalafil in plasma. Method could be applied to determination of tadalafil in plasma for PK and BE studies.